Novel use of polymerase chain reaction to amplify cellular DNA adjacent to an integrated provirus. - Silver, J (1989)
We describe a modification of the polymerase chain reaction technique which allows amplification of cellular DNA adjacent to an integrated provirus given sequence information for the provirus only. The modified technique should be generally useful for studies of insertional mutagenesis and other situations in which one wishes to isolate DNA adjacent to a region of known sequence.